The Relationship Between Factors Influencing Purchasing and Purchase Intention of Smartphones Among Adults in Johor Bahru - Kee Jia Yie ,; Muhammad Ammar Shafi, (Research in Management of Technology and Business, 2023)
Due to lack of support on mobile devices, users are forced to perform their tasks on desktops which frustrates them when they use mobile devices for both communication and entertainment. Another issue is that most Android phone users upgrade to new devices after three to four years of use. Therefore, the purpose of this study is to identify the relationship between factors influencing purchasing and purchase intention of smartphones among adults in Johor Bahru. The quantitative approach was used in this study. Using online Google Forms, 384 questionnaires were distributed to adult consumers aged 20–49 in Johor Bahru. The data was collected and examined using the Statistical Package for Social Science (SPSS), and the response rate was 80.47%. According to the findings of the descriptive analysis, brand was the main factor in the purchase of smartphones among adults in Johor Bahru. The findings showed that there is a significant relationship between brand, price, and product features and the purchase intention of smartphones among adults in Johor Bahru. The limitations of this study included a lack of time, a small number of respondents, unreliable and untruthful answers, and communication difficulties. This study provided some recommendations for future research.